2020
DOI: 10.1001/jamainternmed.2019.7495
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Anti-MRSA vs Standard Antibiotic Therapy and Risk of 30-Day Mortality in Patients Hospitalized for Pneumonia

Abstract: IMPORTANCEUse of empirical broad-spectrum antibiotics for pneumonia has increased owing to concern for resistant organisms, including methicillin-resistant Staphylococcus aureus (MRSA). The association of empirical anti-MRSA therapy with outcomes among patients with pneumonia is unknown, even for high-risk patients.OBJECTIVE To compare 30-day mortality among patients hospitalized for pneumonia receiving empirical anti-MRSA therapy vs standard empirical antibiotic regimens. DESIGN, SETTING, AND PARTICIPANTSRetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 49 publications
2
57
2
1
Order By: Relevance
“…MRSA has also gained importance in geriatrics medicine as it has been associated with higher mortality rates in elderly patients even after using anti-MRSA therapy. [ 12 ] In this study, the prevalence of MRSA among the anterior nares of the healthy medical students of was found too far lower than other studies on the medical students and healthcare workers from other parts of India. [ 26 27 28 ] The student with MRSA nasal carriage was advised for mupirocin ointment treatment.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…MRSA has also gained importance in geriatrics medicine as it has been associated with higher mortality rates in elderly patients even after using anti-MRSA therapy. [ 12 ] In this study, the prevalence of MRSA among the anterior nares of the healthy medical students of was found too far lower than other studies on the medical students and healthcare workers from other parts of India. [ 26 27 28 ] The student with MRSA nasal carriage was advised for mupirocin ointment treatment.…”
Section: Discussioncontrasting
confidence: 64%
“…[ 11 ] Even after treating MRSA infections with empirical anti-MRSA therapy the mortality rate remains high specially among the geriatric patients. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…All patients should undergo culture and sensitivity testing before antibiotics administration, and the use of antibiotics targetting resistant bacteria should not be used as empirical therapy. It has also been found by recent studies that empirical therapy targetting resistant species has no mortality benefit over the use of standard antibiotics, and only contributes to the phenomenon of increased resistance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, subsequent research showed that not only was this phenomena probably limited to relatively few centers, 16 the introduction of HCAP resulted in a massive increase in broad-spectrum antibiotic use 17 that almost certainly harmed more patients than it benefited. 17,18 The new guidelines recommend that P. aeruginosa and MRSA are only covered if risk factors are present AND local data have confirmed that these pathogens are problematic. Acknowledging that many centers may not have local data currently, the guidelines further recommend that sputum and blood cultures be taken whenever broad-spectrum antibiotic coverage is used to generate this information.…”
Section: Advances In Treatment: Antimicrobials For Pneumoniamentioning
confidence: 99%
“…Introduced in the 2005 hospital-acquired pneumonia guidelines, 15 HCAP was an attempt to recognize that in some centers there was a much larger number of patients presenting with pneumonia and organisms not covered by standard empiric therapy, typically Pseudomonas aeruginosa and MRSA. Fortunately, subsequent research showed that not only was this phenomena probably limited to relatively few centers, 16 the introduction of HCAP resulted in a massive increase in broad-spectrum antibiotic use 17 that almost certainly harmed more patients than it benefited. 17,18 The new guidelines recommend that P. aeruginosa and MRSA are only covered if risk factors are present AND local data have confirmed that these pathogens are problematic.…”
Section: Advances In Treatment: Antimicrobials For Pneumoniamentioning
confidence: 99%